A comparative finite analysis of the mechanical behavior of ProTaper NEXT and WaveOne rotary files - Omar, Nada (2021)
Finite element analysis was used to evaluate the stress distribution, estimate the residual stresses, bending, and amount of displacement of two nickel-titanium instruments manufactured by the same M-wire technology but with different cross-section. The WaveOne file showed higher torsional stresses accumulation than those accumulated in the ProTaper NEXT. While the ProTaper NEXT showed more bending and file displacement than those showed by WaveOne file.